2022
DOI: 10.21037/tcr-22-1216
|View full text |Cite
|
Sign up to set email alerts
|

Pneumocystis jirovecii pneumonia in non-Hodgkin’s lymphoma after rituximab-based chemotherapy: a case series

Abstract: Background: The incidence of Pneumocystis jirovecii pneumonia (PCP) has been increasing in patients with hematologic malignancies due to the use of glucocorticoid therapy and immunosuppressive medication. The reports of PCP in non-Hodgkin's lymphoma (NHL) after rituximab-based chemotherapy are still rare. We reported a case series of PCP in NHL to show the clinical features and prognosis in those patients.Methods: We conducted a retrospective review of 15 NHL patients who developed PCP after rituximabbased che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Studies have reported the varying incidence of HIV-related PJP throughout the developing world [ 43 , 44 , 45 ]. Patients with hematologic malignancies are known to have higher levels of immunosuppression [ 46 ], and the incidence of PJP has been increasing in subjects with hematologic malignancy [ 47 ]. Patients with antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) were at higher risk for PJP infection [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported the varying incidence of HIV-related PJP throughout the developing world [ 43 , 44 , 45 ]. Patients with hematologic malignancies are known to have higher levels of immunosuppression [ 46 ], and the incidence of PJP has been increasing in subjects with hematologic malignancy [ 47 ]. Patients with antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) were at higher risk for PJP infection [ 48 ].…”
Section: Discussionmentioning
confidence: 99%